Implementation of Program Sekolah Penggerak in Improving the Leadership Quality of Elementary Schools in Lebak District, Indonesia - Rusdin Rusdin; Wawan Wahyuddin; Nana Suryapermana (International Journal of Science Education and Cultural Studies, 2023)
This study aims to analyze the Program Sekolah Penggerak in efforts to improve the quality of principal leadership and the supporting and inhibiting factors in the implementation of the Program Sekolah Penggerak. The research method uses qualitative research methods. The research was conducted at the public elementary school in Lebak Regency. Research data was collected using observation, interview, and documentation techniques. Furthermore, the data were analyzed using a qualitative descriptive approach. The results of this study indicate that the implementation of the Program Sekolah Penggerak is inseparable from five interventions, namely consultative and asymmetric assistance, strengthening school human resources, new paradigm learning, data-based planning, and school digitalization. Supporting factors for the Program Sekolah Penggerak at public elementary schools in Lebak regency are local government support, productive-age human resources, facilities, and infrastructure, as well as support from parents and the community. The obstacles faced were budget constraints and the impact of the implementation of the Program Sekolah Penggerak, namely the existence of policies oriented towards fulfilling student learning and budget policies oriented towards fulfilling teacher-student learning, which required them to get out of their comfort zone. By participating in training activities to strengthen school human resources, there is motivation and enthusiasm for new teachers to accept different learning models because students are served based on their interests and learning styles.